The efficacy and safety of Sanqi Qushi Granule in patients with idiopathic membranous nephropathy --protocol of a multicenter, randomized control trial (SQ-AUTUMN) - Chuang Li; Wenjun Shan; Xing Liang; Qinghua Zhang; Xindong Qin; Sha Jiang; Xiaofan Hong; Lijuan Wang; Ping Li; Haowen Gu; Yi Wang; Kun Bao (BMC, 2023)
Abstract Background Adult nephropathy is mainly caused by idiopathic membranous nephropathy (IMN). In cases of proteinuria, Modified Ponticelli Regimens (MPR) are often successful. However, it can cause adverse side effects. Oral Sanqi Qushi Granule (SQG) with MPR is effective in patients with IMN. However, whether it can improve the remission rate of IMN and shorten the remission time is unknown. In this trial, SQG with MPR on IMN will be evaluated clinically for its efficacy and safety. Methods We will randomly assign IMN patients who meet the criteria to receives SQG plus cyclical Cyclophosphamide (CTX)/steroids or with placebo plus cyclical CTX/steroids for 6 months. A 12-month follow-up will be conducted on them. Status of remission will be used to assess treatment efficacy. Discussion This study aims to appraise whether treatment with SQG plus cyclical CTX/steroids is superior to placebo plus cyclical CTX/steroids in the remission rate of patients with adult IMN. Adverse events of SQG plus MPR will be also evaluated for further researches about Chinese Medicine and MPR on whether it can improve the remission rate of IMN in half a year and shorten the remission time and relieve adverse effects will also be clarified. Trial registration Chinese Clinical Trial Registry ChiCTR2200061953 . Registered on 13 July 2022.